The Mad Wolf's daughter - Magras, Diane (Puffin Books, 2019)
When invading knights capture Drest's father, the Mad Wolf of the North, and her brothers, she is left behind. Determined to rescue her family, she sets across Scotland with a wounded knight as a captive and encounters a bandit, saves a witch from the stake, and travels through unwelcoming villages. But the closer she gets to saving her family, the more she learns about her family's war-band and their vicious reputation. Drest has to decide if she is her father's daughter or something else.